Desain Evaluasi Digital Berbasis HOTS Pada Pembelajaran Pendidikan Pancasila Kelas V Sekolah Dasar - Jefri Oktaviandi; Miaz, Yalvema; Erita, Yeni; Alfarisi Nirya , Haikal; Zulfi , Aditra (Journal of Practice Learning and Educational Development, 2026)
Pancasila Education learning at the elementary school level requires evaluation methods that can measure higher-order thinking skills (HOTS) in line with the demands of the Merdeka Curriculum. However, evaluation practices in schools are still dominated by conventional instruments that have not optimally developed students’ analytical, evaluative, and creative abilities. This study aims to design a HOTS-based digital evaluation for the topic of cultural diversity in Grade V elementary schools by utilizing Google Forms as an evaluation medium. The research employed a descriptive qualitative approach, with data collected through document analysis of teaching modules, learning outcomes, learning objectives, and documentation of the digital evaluation design process. The results indicate that the teaching module applies a Problem Based Learning model, with learning objectives at the C4, C5, and C6 cognitive levels, thus requiring evaluation instruments aligned with HOTS characteristics. This study produced 20 case-based multiple-choice questions developed based on a digital evaluation blueprint and implemented using Google Forms. The digital evaluation was effective in measuring students’ analytical, evaluative, and problem-solving abilities, while also providing ease of administration, automatic scoring, and integration of digital literacy. This research contributes to the development of a relevant and modern evaluation model suitable for 21st-century learning.